Towards autistic flow theory: A non‐pathologising conceptual approach - Gemma Williams (Journal for the Theory of Social Behaviour, 2024)
Flow states are heightened moments of concentration, motivation and enjoyment, leading to total absorption in the present moment. A striking parallel exists between flow states and phenomenological accounts of autistic daily life. We analyse the components of flow theory alongside autistic autobiographical accounts to explore similarities and differences, in doing so moving toward an understanding of autistic flow theory. We highlight the considerations and opportunities this may hold for future autism research, in particular the advantage that this offers a non-pathologising approach to researching autism, one which helps to explain contextualised behaviour (i.e., alignment between the situation and what is happening in one's mind). Drawing on autistic autobiographical accounts, we outline four principles: (1) autistic people are uniquely placed to discover and manage flow; (2) autistic flow may qualitatively diverge from traditional models of flow; (3) difficulties maintaining and exiting flow for autistic people highlight a need to examine transitions into and out of flow; and, (4) internal and external constraints to flow highlight there is unrealised autistic potential yet to be discovered. The implications of an autistic flow theory are discussed in terms of how it can impact (a) our conceptual understanding of autism providing alternative explanations to previously researched phenomena, and (b) how we build enabling environments for autistic people that allow flow to flourish across educational practice, wellbeing and research contexts.